Dialogue of Friendship: A Phenomenological Study of Christian-Muslim Interreligious Dialogue and Peacebuilding in Mindanao, Philippines - Jesster B. Fonseca (Indonesian Character Journal, 2026)
Religions were usurped, justifying atrocious acts against each other since time immemorial. To name a few in contemporary times, the Marawi siege of 2017, and the September 11, 2001, attack against the United States of America. Recently, the Israeli-Palestinian Gaza war of 2023 reignited more than half a century of conflict. Now, we have the US-led Israel war against Iran, and US President Donald Trump was heard trumpeting his messianic role in saving Christianity from barbarous deeds of the Middle-Eastern states, justifying now his more atrocious deeds against them. This study investigates the role of interreligious dialogue in the life of Christians and Muslims living in Southern Philippines, also known as Mindanao, in this post-colonial period. It intends to understand the state or condition of dialogue between adherents of religions, particularly, the Muslims and Christians of Mindanao, as to how interreligious dialogue brought about mutual understanding, peaceful co-existence, cooperation, and harmonious living between them. And by this, the findings can hopefully contribute to the establishment of peace in other places and peoples in conflict by indicating the salient points that serve as learning considerations. Thus, to find the answer, the researcher worked on knowing the lived experiences of co-researchers who are advocates, practitioners, and scholars of interreligious dialogue (IRD) in Mindanao. And by this, the data gathered and analyzed became a resource of learning in the work of the peace process via interreligious dialogue among adherents of different religions. Phenomenology was employed as its interpretive framework in the data supplied by 4 co-researchers.  All of them have dedicated years working and studying, Christians and Muslims thriving and coexisting in Mindanao. In the final analysis, the success story of interreligious dialogue in Mindanao was attributed to the dialogue of friendship between Christians and Muslims thriving there. In their dialogue of friendship, they were able to affirm each other’s identity and history, surpassing challenges they had encountered along the way.